P255 Benchmarking of an interventional pleural service. (December 2018) - McCracken, DJ; Bedawi, E; Hassan, M; Mercer, R; Asciak, R; Rahman, NM
Abstract : Introduction: The current prevalence of pleural disease remains somewhat unclear and estimates are based on outdated epidemiological studies. This creates difficulty in the planning and organisation of pleural services. A local population of 6 55 000 is served by the Oxford Pleural Unit with other referrals from within the trust increasing this to 8 05 000. External tertiary referrals may also be received from a wider area covering a population of approximately 2.5 million. Review and analysis of the work of the unit provides a greater understanding of the prevalence of pleural disease requiring intervention and allows improvement in the design and structure of pleural services. Method: All patients undergoing a pleural procedure under the Oxford Pleural Unit have had their case subsequently discussed at a pleural MDT since its inception in July 2015. Complete follow up data is collected prospectively from this meeting and maintained in a comprehensive database. Analysis of this data allows benchmarking of a regional tertiary pleural service. Results: The pleural MDT facilitated 1422 discussions involving more than 1250 procedures in 870 patients over a three year period. This included a wide range of pleural interventions and equates to approximately 12 procedures per week (see table 1). Our data suggests that thoracoscopy is required in 8.6 patients per 1 00 000 population per year. An approximate autopleurodesis rate of 36% in patients with an indwelling pleural catheter (IPC) is in keeping with previously published data and suggests the requirement for ongoing specialist nurse input in many cases. Discussion: These figures allow for benchmarking of the procedural component of a specialist pleural service, however provide a modest underestimate of the overall burden of interventional pleural work undertaken in Oxford due to further procedures undertaken on the ward, by radiology or in district general hospitals within the area. Increased capacity of the service following the recruitment of two clinical fellows has led to an increase of 78 procedures over a 6 month period representing a high demand and a clinical need for a timely, high quality specialist pleural service.